One for the hooks : a crochet mystery - Hechtman, Betty, 1947- (Hechtman, Betty, 1947- Crochet mystery., 2021)
When Sloan Renner, the woman helping her friend - Miami - clean her house, is found dead under a pile of smelly seafood, Molly Pink, a member of the Tarzana Hookers crochet club, must unravel the clues to prove that the Sloan's death was no accident.